2021
DOI: 10.1212/wnl.0000000000011151
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Practice Guidelines by the Infectious Diseases Society of America, American Academy of Neurology, and American College of Rheumatology

Abstract: This evidence-based clinical practice guideline for the prevention, diagnosis, and treatment of Lyme disease was developed by a multidisciplinary panel representing the Infectious Diseases Society of America (IDSA), the American Academy of Neurology (AAN), and the American College of Rheumatology (ACR). The scope of this guideline includes prevention of Lyme disease, and the diagnosis and treatment of Lyme disease presenting as erythema migrans, Lyme disease complicated by neurologic, cardiac, and rheumatologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 5 publications
2
31
0
Order By: Relevance
“…Furthermore, the safety of doxycycline concerning dental staining, given to children under 8 years of age, has been under debate [ 12 14 ] and recent guidelines have come to different recommendations. German guidelines from 2020 have kept the recommendation of doxycycline to children 9 years of age and up [ 23 ], while guidelines from the American Academy of Neurology have stated that oral doxycycline may be considered over intravenous treatment in children of all ages who can tolerate oral antibiotics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the safety of doxycycline concerning dental staining, given to children under 8 years of age, has been under debate [ 12 14 ] and recent guidelines have come to different recommendations. German guidelines from 2020 have kept the recommendation of doxycycline to children 9 years of age and up [ 23 ], while guidelines from the American Academy of Neurology have stated that oral doxycycline may be considered over intravenous treatment in children of all ages who can tolerate oral antibiotics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients were treated with 3 weeks of oral doxycycline in accordance with IDSA Guidelines (16). Lyme patients were seen regularly over the course of 2 years for a total of 5 study visits (before and immediately after treatment, and 1 month, 6 months, and 2 years posttreatment).…”
Section: Johns Hopkins University (Jhu) Cohortmentioning
confidence: 99%
“…However, while the CDC reports that the majority of patients develop an EM rash, Lyme-associated rashes can be mistaken for other conditions or may go unnoticed or unreported due to their location, highly variable appearance, and/or transient nature (12)(13)(14)(15). The Infectious Diseases Society of America (IDSA) recommends serologic testing to support a diagnosis of Lyme disease for patients with atypical EM rash, as well as for patients in appropriate epidemiologic settings who have symptoms and exposure compatible with disseminated infection, such as arthritis, central nervous system involvement, or acute myocarditis/pericarditis (16). Some studies have reported that EM rash is absent in 50% to 60% of laboratory-confirmed cases of Lyme (17,18), highlighting the difficulty of reaching a definitive clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors refer to the ILADS guideline (Cameron et al, 2014 ), which in itself does not contain any diagnostic criteria. Without unambiguous criteria, one cannot ensure that these individuals were in fact patients with LB (Stanek et al, 2011 ; Lantos et al, 2021 ). It is also unclear what is meant by “early LD” and “late LD.” Would Lyme neuroborreliosis (LNB) be classified as early or late LD, for example (Koedel and Pfister, 2017 )?…”
Section: Selection Criteria Lb Patientsmentioning
confidence: 99%